Task-Based Instruction in Vocational ESP: A Qualitative Inquiry into Lecturers’ Experiences at UKI Toraja - Charlie Baka; Markus Deli Derik Allo; Nilma Taula’bi’; Elim Trika Sudarsi (Eduvelop: Journal of English Education and Development, 2026)
This research explores lecturers’ experiences with implementing Task-Based Instruction (TBI) in teaching English to mechanical engineering students at UKI Toraja. Using a qualitative descriptive design, data were collected through semi-structured interviews with English lecturers involved in the engineering program. Thematic analysis revealed four major findings. First, lecturers expressed positive perceptions toward TBI, noting that task-based activities promoted active learning and made English more relevant to students’ vocational needs. Second, TBI was implemented through authentic, engineering-related tasks such as describing machine parts, explaining work procedures, and presenting technical solutions, although lecturers noted that designing such tasks required additional preparation. Third, challenges emerged in applying TBI, including students’ low English proficiency, limited resources, large class sizes, and time constraints. Finally, lecturers reported that students generally responded positively to TBI, showing higher motivation and engagement when tasks were concrete, visual, and connected to real engineering contexts. Despite existing obstacles, the study concludes that TBI has strong potential to enhance English learning in vocational settings. Recommendations include improving institutional support, enriching teaching resources, and strengthening collaboration between English and engineering lecturers to optimize TBI implementation at UKI Toraja.